2019
DOI: 10.1155/2019/6382934
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Compressive and Tensile Characteristics of a New Type of Ultra‐High‐Molecular Weight Polyethylene (UHMWPE) and Polyvinyl Alcohol (PVA) Fibers Reinforced Concrete

Abstract: The dynamic mechanical properties of concrete materials are important parameters for evaluating the safety performance of concrete structures under dynamic loads. Fiber cement-based materials have been widely used in the construction projects due to their strength, toughening, and cracking resistance. In this study, we conducted experimental and theoretical studies on dynamic compression and tensile mechanical properties of different proportions of new-type fiber concrete. A Split-Hopkinson pressure bar equipm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(33 reference statements)
2
7
0
Order By: Relevance
“…Nowadays, cementitious composites are extensively used in civil engineering construction due to its better cracking resistance, durability, toughening, and strength 1,2 . Also, the addition of fibers into cementitious composites can further improve the flexural strength, toughness, energy absorption, resistance to impact, durability, shear, tensile, and compressive strengths 3–10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, cementitious composites are extensively used in civil engineering construction due to its better cracking resistance, durability, toughening, and strength 1,2 . Also, the addition of fibers into cementitious composites can further improve the flexural strength, toughness, energy absorption, resistance to impact, durability, shear, tensile, and compressive strengths 3–10 .…”
Section: Introductionmentioning
confidence: 99%
“…Fiber reinforced cementitious composite (FRCC) had been developed to control the brittleness of cement‐based composites and improves the resistance against cracking 1,11 . Dynamic properties of composite materials are important in order to evaluate the safety performance of composite structures 2 . FRCC had a great advantage in earthquake‐resistant structures than that of plain composite 12 .…”
Section: Introductionmentioning
confidence: 99%
“…e results of the numerical analysis show good agreements with those reported in the literature. e different types of loads can store elastic energy before damage, and this energy storage accelerates and develops damage mechanism [25][26][27][28][29][30][31][32][33]. In the present numerical analysis, it has been observed that the shape of +5.442e + 00 +4.535e + 00 +3.628e + 00 +2.721e + 00 +1.814e + 00 +9.070e -01 +3.576e -07 -9.070e -01 -1.814e + 00 -2.721e + 00 -3.628e + 00 -4.535e + 00 -5.442e + 00 (a) +5.380e + 00 +4.483e + 00 +3.586e + 00 +2.690e + 00 +1.793e + 00 +8.966e -01 +1.192e -07 -8.966e -01 -1.793e + 00 -2.690e + 00 -3.586e + 00 -4.483e + 00 -5.380e + 00 +5.442e + 00 +4.535e + 00 +3.628e + 00 +2.721e + 00 +1.814e + 00 +9.070e -01 +3.576e -07 -9.070e -01 -1.814e + 00 -2.721e + 00 -3.628e + 00 -4.535e + 00 -5.442e + 00 +5.380e + 00 +4.483e + 00 +3.586e + 00 +2.690e + 00 +1.793e + 00 +8.966e -01 +1.192e -07 -8.966e -01 -1.793e + 00 -2.690e + 00 -3.586e + 00 -4.483e + 00 -5.380e + 00…”
Section: Numerical Analysis Discussion and Verification Of The Resultsmentioning
confidence: 99%
“…With the same cracking mechanism, PVA member cracking can reach a saturated state with small crack spacing, until localization of a random single crack occurs. Osman et al (2019) noted that there is a bridging effect of fiber which inhibit the expansion of cracks during testing and restrain the crack width. Furthermore, it can enhance the lateral restraint performance of concrete when it is damaged.…”
Section: Crack Pattern and Failure Modesmentioning
confidence: 99%
“…It was observed also that no signs of spalling appeared on columns containing PVA fibers. This may be attributed to the fiber bridging effect, or in other words, when concrete exposed to high temperature, the PVA fibers melts creating paths to escape water vapor, which was captured in pore structure of concrete, in order to give concrete room to breathe, to prevent explosions and, in turn, to increase its resistance (Osman et al, 2019). Cao et al (2019) also observed no spalling in samples with PVA exposed to elevated temperature.…”
Section: Load-deflection Curves For Studied Columnsmentioning
confidence: 99%